STUDENTS’ SPEAKING ANXIETY IN SPEAKING SKILLS IN THE CLASSROOM AS A FOREIGN LANGUAGE FOR THE 2nd GRADE AT SMA NEGERI 1 PAREPARE - Sudarmanto, Sudarmanto; Patahuddin, Patahuddin; Lestari, Putri Veronica (LPPM Institut Pendidikan Nusantara Global, 2023)
To speak English, someone, especially among students, needs to master several verbs, and one of the obstacles to speaking English is the lack of verbs among students. Therefore, students face various obstacles. Anxiety is one of the biggest obstacles for students. Therefore, the purpose of this research is to find out what is students' anxiety and what factors cause students' anxiety when speaking in English in class. The sample of this study was MIPA 5 students of XI class of SMAN 1 Parepare which consisted of 35 students. The approach used in this study is descriptive research and qualitative. This study uses two research instruments namely Horowitz et al. (1986) used the Foreign Language Classroom Anxiety Scale (FLCAS) and interviews. The questionnaire had 33 items consisting of 9 positive and 24 negative statements on a Likert scale of 1-5 points, while the interview consisted of 10 questions. According to the survey's findings, there was only 1 respondent with a